Elaboración de un análisis comparativo de los principales modelos de desarrollo de proyectos disponibles en la actualidad (2015)
"Within the framework of the research and innovation project:" Update of the Project Development Model proposed by the School based on a comparative analysis of existing national and international models and of the particular needs of the industry in Colombia "prepared by the Center for Studies in Development and Integral Management of Projects of the Colombian School of Engineering (CEP), it is established as one of the specific objectives of the project to carry out a comparative analysis of the main national and international models of development of existing projects currently. For this the CEP raised the possibility that postgraduate students elaborate this analysis, the central theme of the present work of degree. Based on the theoretical and conceptual solidity provided by the Specialization in Development and Integral Project Management, it was possible to determine the key elements to carry out a successful analysis and subsequently consolidate the own model that the Project Unit of the School has been working on for several years. years, this with the aim of spreading the model in academic spaces and in the national industry ... "- Extract of the document